2014
DOI: 10.1016/j.jdent.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different sonic activation protocols on debridement efficacy in teeth with single-rooted canals

Abstract: Objectives The effects of different EndoActivator® (EA) sonic activation protocols on root canal debridement efficacy were examined. Methods Root canals in 48 single-rooted teeth were instrumented, irrigated initially with NaOCl and divided into 6 groups (N=8) based on the application time of QMix (antimicrobial calcium-chelating irrigant), and the time and sequence of EA irrigant activation - Positive Control: 90 sec QMix; Negative Control: 90 sec saline; Group 1A: 15 sec QMix + 15 sec QMix with EA-activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 38 publications
(37 reference statements)
5
14
0
2
Order By: Relevance
“…Auxiliary devices may also create a flux-reflux mechanism that propels debris and microorganisms out of the root canal system. The present results are similar to those of recent report (22) that evaluated the effects of QMix with different sonic activation protocols on canal debridement and concluded that, with 30 s of activation, this solution results in better cleaning and significantly reduces the minimum duration required for action. It is important to point out, however, that agitation of root canal irrigants may increase apical extrusion in conjunction with factors such as root canal anatomy and the technique used.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Auxiliary devices may also create a flux-reflux mechanism that propels debris and microorganisms out of the root canal system. The present results are similar to those of recent report (22) that evaluated the effects of QMix with different sonic activation protocols on canal debridement and concluded that, with 30 s of activation, this solution results in better cleaning and significantly reduces the minimum duration required for action. It is important to point out, however, that agitation of root canal irrigants may increase apical extrusion in conjunction with factors such as root canal anatomy and the technique used.…”
Section: Discussionsupporting
confidence: 92%
“…Although this suggests that the absence of an associated device can be compensated for by increasing the duration of solution action, care is necessary as the toxicity of an agent usually increases with time (14). These results are in agreement with those of a previous study (22), which reported that root canal walls were cleaner, and the time required for satisfactory SL removal was shorter, for sonic activation of QMix than for conventional needle irrigation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding the use of S instruments, Niu et al 12 studied the activation of irrigants using the EndoActivator system for a period of 30 to 60 seconds. Observing the samples by SEM, they said that activation of the irrigant maximized the removal of detritus and reduced the time required for cleaning compared with conventional irrigation.…”
Section: Discussionmentioning
confidence: 99%